دور المرأة في الاقتصاد - Rafidah Bt Awang; رافيده أونج (Kolej Universiti Islam Malaysia, 2022)
This research is about the role of women in the economic development today. The aim of this topic to be debuted in to know more about women's development in all experts based on Islamic Syarie. This research uses the approach of library research on the main source. The result of this research is the researcher ford out that the role of women is very important in making contributions in the family and country's economic development, parallel with the responsibilities of the men. It is proven that women are becoming smarter and more prominent all fields at this millennium. The writer hopes that the worker women are just at dividing time between work and family for the well -beiy of the Islamic Ummah.